Linking radial growth patterns and moderate‐severity disturbance dynamics in boreal old‐growth forests driven by recurrent insect outbreaks: A tale of opportunities, successes, and failures. Issue 1 (14th December 2020) - Martin, Maxence; Krause, Cornélia; Morin, Hubert
Abstract: In boreal landscapes, emphasis is currently placed on close‐to‐nature management strategies, which aim to maintain the biodiversity and ecosystem services related to old‐growth forests. The success of these strategies, however, depends on an accurate understanding of the dynamics within these forests. While moderate‐severity disturbances have recently been recognized as important drivers of boreal forests, little is known about their effects on stand structure and growth. This study therefore aimed to reconstruct the disturbance and postdisturbance dynamics in boreal old‐growth forests that are driven by recurrent moderate‐severity disturbances. We studied eight primary old‐growth forests in Québec, Canada, that have recorded recurrent and moderately severe spruce budworm ( Choristoneura fumiferana [Clem.]) outbreaks over the 20th century. We applied an innovative dendrochronological approach based on the combined study of growth patterns and releases to reconstruct stand disturbance and postdisturbance dynamics. We identified nine growth patterns; they represented trees differing in age, size, and canopy layer. These patterns highlighted the ability of suppressed trees to rapidly fill gaps created by moderate‐severity disturbances through a single and significant increase in radial growth and height. Trees that are unable to attain the canopy following the disturbance tend to remain in the lower canopy layers, even if subsequent disturbances create new gaps. This combination of a low stand height typical of boreal forests, periodic disturbances, and rapid canopy closure often resulted in stands constituted mainly of dominant and codominant trees, similar to even‐aged forests. Overall, this study underscored the resistance of boreal old‐growth forests owing to their capacity to withstand repeated moderate‐severity disturbances. Moreover, the combined study of growth patterns and growth release demonstrated the efficacy of such an approach for improving the understanding of the fine‐scale dynamics of natural forests. The results of this research will thus help develop silvicultural practices that approximate the moderate‐severity disturbance dynamics observed in primary and old‐growth boreal forests. Abstract : The analysis of radial growth patterns highlights that boreal old‐growth forests are resistant to recurrent and moderate‐severity disturbances, as understory trees can rapidly fill the resulting gaps. However, trees that are unable to attain the canopy following the disturbance then tend to remain in the lower canopy layers, even if a new disturbance reopens the canopy. Therefore, reaching the canopy represents a once‐in‐a‐lifetime opportunity, where success or failure depends on a relatively short window of time. Résumé: Dans les paysages boréaux, l'accent est désormais mis sur des stratégies de gestion proches de la nature afin de maintenir la biodiversité et les services écosystémiques liés aux vieilles forêts. Le succès de ces stratégies dépend toutefois d'une compréhension fine de la dynamique de ces forêts. Les perturbations de sévérité modérée ont ainsi été récemment reconnues comme étant d'importants moteurs de la dynamique des forêts boréales, mais l'on sait encore peu de choses de leur influence sur la structure et la croissance des peuplements. Par conséquent, l'objectif de cette étude est de reconstruire les dynamiques de perturbation et post‐perturbation dans les vieilles forêts boréales causées par des perturbations récurrentes de sévérité modérée. Nous avons étudié huit vieilles forêts primaires au Québec, Canada, ayant enregistré des épidémies de tordeuse des bourgeons de l'épinette ( Choristoneura fumiferana [Clem.]) récurrentes et de sévérité modérée au cours du 20ème siècle. Nous avons utilisé une approche dendrochronologique innovante combinant l'étude des patrons et des reprises de croissance pour reconstruire la dynamique de perturbation et post‐perturbation de ces forêts. Nous avons identifié neuf patrons de croissance, observés dans des arbres d'âge, de taille ou de strate de canopée différents, indiquant des dynamiques particulières. Ces patrons ont mis en évidence la capacité des arbres opprimés à rapidement combler les trouées dans la canopée en un unique et significatif accroissement de circonférence et de hauteur. En revanche, les arbres déjà situés dans la canopée ont eu peu d'influence sur la fermeture de ces trouées. En conséquence, les arbres dominants et codominants étaient les plus fréquents dans la canopée. Les résultats de cette étude soulignent la résistance des vieilles forêts boréales aux perturbations récurrentes et de sévérité modérée, car les arbres du sous‐étage peuvent rapidement combler les trouées qui en résultent. Cependant, les arbres incapables d'atteindre le sommet de la canopée à la suite d'une perturbation resteront ensuite souvent dans les strates inférieures de la canopée, même si des perturbations subséquentes créent ensuite de nouvelles trouées. La combinaison de la faible hauteur des arbres typique des forêts boréales, des perturbations périodiques et de la rapide fermeture des trouées forme des peuplements avec une structure verticale ressemblant à celle des forêts équiennes. Globalement, cette étude souligne la résistance des vieilles forêts boréales en raison de leur capacité à supporter des perturbations répétées de sévérité modérée. De plus, l'étude combinée des patrons et des reprises de croissance démontre l'efficacité de cette approche pour reconstruire la dynamique à échelle fine des forêts naturelles. Les résultats de cette recherche contribueront ainsi à développer des pratiques sylvicoles analogues à la dynamique de perturbation de sévérité modérée observée dans les vieilles forêts primaires des paysages boréaux.